Societal Security and Crisis Management
XVII, 397 p. 10 illus.
Keywords: This book studies governance capacity and governance legitimacy for societal security and crisis management. It highlights the importance of building organizational capacity by focusing on the coordination of public resources and underscores the relevance of legitimacy by emphasizing the importance of public perceptions, attitudes, and trust vis-à-vis government arrangements for crisis management. The authors explore several cases and identify relevant dimensions concerning performance, capacity and legitimacy across different countries. It is an ideal volume for audiences interested in public administration, public policy, crisis management and security studies. Per Lægreid is Professor at the Department for Administration and Organization Theory, University of Bergen, Norway. Lise H. Rykkja is Associate Professor at the Department for Administration and Organization Theory, University of Bergen, Norway, and Research Professor at Uni Research Rokkan Centre, Norway. .